Peran Pondok Pesantren Modern Gontor Sebagai Instrumen Multitrack Diplomacy Pendidikan dalam Kerjasama Internasional - Amalia, Novi (Nation State: Journal of International Studies, 2019)
Islamic boarding schools are one of the educational institutions that are in great demand by many Muslims in Indonesia starting from the middle to lower classes of society to middle and upper society. The role of the pesantren in educating the younger generations in the millennial era has quite a lot of impact. The current phenomenon is that many education systems only prioritize school education in the classroom without understanding character education. One of the pesantren which is quite long and in demand and produces many alumni who are engaged in government and professional fields is Pondok Modern Darussalam Gontor (PMDG). PMDG is Islamic boarding schools which have considerable domestic and foreign cooperation. This pattern of diplomacy and cooperation will have an impact on the existence of PMDG in pesantren education. In globalization era, diplomacy involves not only the state but also non-state actors. Diplomacy Line 5 (Educational Pathway) have a main goal to advancing the education. Educational institution can influence the thinking of learners, moreover it can be seen that the cooperation carried out by the pesantren educational institutions are many from foreign institutions and even students who demand knowledge from many other countries.